Two-colour chewing gum mixing ability: digitalisation and spatial heterogeneity analysis - Weijenberg, R. A. F.; Scherder, E. J. A.; Visscher, C. M.; Gorissen, T.; Yoshida, E.; Lobbezoo, F. (Journal of oral rehabilitation, 2013)
Summary Many techniques are available to assess masticatory performance, but not all are appropriate for every population. A proxy suitable for elderly persons suffering from dementia was lacking, and a two‐colour chewing gum mixing ability test was investigated for this purpose. A fully automated digital analysis algorithm was applied to a mixing ability test using two‐coloured gum samples in a stepwise increased number of chewing cycles protocol (Experiment 1: n = 14; seven men, 19–63 years), a test–retest assessment (Experiment 2: n = 10; four men, 20–49 years) and compared to an established wax cubes mixing ability test (Experiment 3: n = 13; 0 men, 21–31 years). Data were analysed with repeated measures anova (Experiment 1), the calculation of the intraclass correlation coefficient (ICC; Experiment 2) and Spearman's rho correlation coefficient (Experiment 3). The method was sensitive to increasing numbers of chewing cycles (F5,65 = 57·270, P = 0·000) and reliable in the test–retest (ICC value of 0·714, P = 0·004). There was no significant correlation between the two‐coloured gum test and the wax cubes test. The two‐coloured gum mixing ability test was able to adequately assess masticatory function and is recommended for use in a population of elderly persons with dementia.